Development of hypoallergenic ovalbumin with improving functional properties by AAPH and acrolein treatment. (November 2021) - Sun, Fan; Lv, Liangtao; Huang, Chunyang; Lin, Qian; He, Kan; Ye, Liying; Lin, Xiao; Wu, Xuli
Graphical abstract: Highlights: OVA showed lower allergenicity in vitro and in vivo after oxidation. Oxidation increased digestibility and functional properties of OVA. Oxidation provide a new method to process hypoallergenic OVA. Abstract: Ovalbumin (OVA) is one of the major allergenic proteins in egg that contain numerous functional properties. Here, oxidation-induced changes to the structure, functional properties, and allergenicity of OVA were evaluated after 2, 2′-azobis (2-amidinopropane) dihydrochloride (AAPH) and acrolein treatment. Oxidation complexes were prepared by the lipid peroxidation, which caused structural changes, and increased digestibility, foaming, and emulsifying properties. The IgE-binding capacity of OVA decreased after oxidation. KU812 cell assay showed that the histamine and IL-4 levels decreased upon oxidation with AAPH and acrolein. A mouse model study showed that oxidation caused a reduction in the allergenicity by reducing IgE and IgG1 levels and the production of Th2 cytokines after acrolein (1 mmol/L) and AAPH (5 mmol/L) treatment. Thus, OVA could cause changes to structural and functional properties, modulating Th1/Th2 immunobalance, and reducing potential allergenicity after oxidation by lipid peroxidation, which might provide an effective and potential method to process hypoallergenic OVA.